Expression of genes of cytokines, transcription factors and differentiation antigens in human dendritic cells activated by double-stranded DNA - A. S. Proskurina; K. E. Orishchenko; E. A. Potter; E. V. Dolgova; A. V. Spaselnikova; G. S. Ritter; N. A. Varaksin; T. G. Ryabicheva; O. Y. Leplina; A. A. Ostanin; E. R. Chernykh; S. S. Bogachev (Вавиловский журнал генетики и селекции)
One of the most important properties of extracellular double-stranded DNA related to the treatment of various diseases is its ability to activate eﬀector cells of the immune system (anti-tumor and vaccinal immunity) through dendritic cells (DCs). The stimulatory eﬀect of DNA on DCs is mediated by the TLR9 signaling pathway and/or through a system of cytosolic sensors and is manifested by increased expression of MHC class II antigens and costimulatory molecules and by increased synthesis of immunoregulatory cytokines. In this work, the expression of cytokines, diﬀerentiation antigens and transcription factor genes has been investigated in DCs activated by double-stranded human DNA (i) without any additional factors, (ii) using a lipophilic agent, and (iii) by blocking TLR9 with chloroquine. Evaluation of the DNA eﬀect was carried out after the 6- and 24-hour exposure. It was found that the preparation of double-stranded DNA transfected by Lipofectamine 2000 boosts DCs at the same level as Poly(dA : dT), a synthetic equivalent of double-stranded DNA. It was discovered that combined application of DNA and chloroquine enhances expression of the IFN-α, IFN-β, IFN-γ, IL8, МСР1, VEGF, CD25, and CD83 genes by hour 24 of incubation. It was for the ﬁrst time shown that genomic “self” double-stranded DNA as a mono agent activates mRNA synthesis of cytokines IFN-α, IFN-β, IFN-γ, IL8, IL10, and VEGF in DCs at 6 hours of induction.